Application of Amine-based Ru Compounds in the Olefin Metathesis of Methyl Eugenol: A Comparison with Grubbs Catalysts - Sousa, Denise A.; Meneses, Paulo S.; Gois, Patrik D. S. [UNESP]; Silva, Eliada A.; Junior, Valdemiro P. C. [UNESP]; Lima-Neto, Benedito S.; Silva Sa, Jose L. (Bentham Science Publ Ltd, 2020)
Methyl eugenol olefin metathesis was conducted with non-carbene Ru-complexes ([RuCl2(PPh3)(2)amine]) in the absence and presence of SnCl2 or CuCl2 as additives and their catalytic activities were compared with that of a commercial Grubbs catalyst 2nd Generation (G2).
Keywords: Olefin metathesis; Methyl-eugenol; SnCl2; CuCl2; ruthenium; additives